2014
DOI: 10.14214/df.174
|View full text |Cite
|
Sign up to set email alerts
|

Quality management of forest regeneration activities

Abstract: The purpose of this thesis was to find out what are the main factors that have to be taken into account in planning, controlling and improving the quality of forest regeneration activities. The forest regeneration services provided for the non-industrial privately-owned forests in Southern Finland by the local Forest Owners' Associations (FOAs) were used as an example. Since the original assumptions of quality management were not completely valid in this context, Lillrank's classification of production process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 92 publications
(170 reference statements)
0
10
0
1
Order By: Relevance
“…With respect to the target seedling density of 1800 pl ha -1 set by Finnish forest management practice recommendations by the Tapio Forestry Development Centre (Äijälä et al 2014), planting quality was excellent in Articles III-V. The average number of Norway spruce seedlings planted manually in southern Finland has been reported as 1388 pl ha -1 (SD 378) (Kankaanhuhta 2014), which is below the recommended target (Äijälä et al 2014). Planting machines plant seedlings deeper than manual worker (Luoranen et al 2011, Luoranen andViiri 2016) and deeply-planted seedlings have been reported to survive and grow better than those planted at more shallow depths (Luoranen and Viiri 2016).…”
Section: Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…With respect to the target seedling density of 1800 pl ha -1 set by Finnish forest management practice recommendations by the Tapio Forestry Development Centre (Äijälä et al 2014), planting quality was excellent in Articles III-V. The average number of Norway spruce seedlings planted manually in southern Finland has been reported as 1388 pl ha -1 (SD 378) (Kankaanhuhta 2014), which is below the recommended target (Äijälä et al 2014). Planting machines plant seedlings deeper than manual worker (Luoranen et al 2011, Luoranen andViiri 2016) and deeply-planted seedlings have been reported to survive and grow better than those planted at more shallow depths (Luoranen and Viiri 2016).…”
Section: Qualitymentioning
confidence: 99%
“…The buried humus layers will decompose and provide nutrients to the seedling over the next few years, and capillary action raises water from the ground so the seedlings are not solely dependent on rainwater (Luoranen et al 2007). Selecting mounding over patching or disc trenching produces better results, as seedling growth is enhanced in the mounded spots (Heiskanen et al 2013;Kankaanhuhta 2014). Soil preparation in general also has a negative impact in terms of enhancing the growth of unwanted tree species that disturb the development of coniferous crop trees (Saksa et al 1990).…”
Section: Reforestation In Finlandmentioning
confidence: 99%
See 3 more Smart Citations